Corpus to curriculum: Developing word lists for adult learners of Welsh - Tess Fitzpatrick (Applied Corpus Linguistics, 2023)
The launch of a language's first comprehensive general corpus promises a sea-change in teaching and learning resources. Effective transition from corpus to classroom is not necessarily straightforward, though; expert and end-user input is essential for the potential of the corpus resource to be realised. This paper outlines the process by which fit-for-purpose vocabulary lists were derived from the new National Corpus of Contemporary Welsh (Corpws Cenedlaethol Cymraeg Cyfoes – CorCenCC). The immediate purpose in this case was to inform the revision of A1 and A2 level course materials for adult learners. A longer-term aim was to put in place a method by which vocabulary lists for more advanced level learners and learners of different ages could be extracted and developed from the corpus. The new corpus means that for the first time, the Welsh language curriculum is able to use word frequency information; teaching and assessment materials in major languages have been informed by word frequencies for several decades. Raw frequency lists, though, include troublesome content, and can exclude items with high relevance to learners. This paper demonstrates how, by working in partnership, Welsh language curriculum writers, assessors, language experts and corpus linguists can effectively manipulate corpus data into curriculum content. The methods and approaches reported here are replicable for use in other language contexts.